Effect of Female Board of Commissioners, Managerial Ownership and Debt Policy on Tax Aggressiveness - Indah Oktari Wijayanti; Susanti Usman; Ratih Juwita; Erna Kustyarini; Ayatullah Al Quddus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this article is to analyze the influence of female commissioners, managerial ownership and debt policy on tax aggressiveness. This article is based on agency theory, namely to understand the relationship between variables. The object of this article is a mining sector company, the Coal subsector on the Indonesian Stock Exchange (BEI) is used as a research object. The sample used was 15 companies during 2016-2018. The method used in sampling is purposive sampling. Data analysis uses classical assumption tests and hypothesis testing using the multiple linear regression method. The results of the research show that Women's Board of Commissioners, Managerial Ownership and Debt Policy have no influence on Tax Aggressiveness. The control variable measurement of leverage has a significant relationship to tax aggressiveness and measurements of company age, company size and probability do not have a significant relationship to Tax Aggressiveness.